The Effect of Education Using Video Media on Knowledge Level and the Selection of Long-Term Contraceptive Methods (MKJP) Among Third Trimester Pregnant Women at Puskesmas Pulosari, Pemalang Regency, in 2025 - Aliyatus Sya’ni; isnaeni rofiqoch (Proceedings Series on Health & Medical Sciences, 2026)
Background: Education through video media is one of the tools used in counseling to enhance understanding. The selection of long-term contraceptive methods (MKJP) is often influenced by limited knowledge, lack of spousal support, and cultural factors. Therefore, midwives play a crucial role in addressing these barriers through educational interventions. A preliminary study conducted in the service area of Puskesmas (Community Healthcare Center) Pulosari, Pemalang Regency, found that only 10.6% of family planning participants used MKJP, while 89.4% used non-MKJP. Objective: This study aimed to determine the effect of education using video media on the knowledge level and selection of MKJP among third-trimester pregnant women at Puskesmas Pulosari. Methods: This was a quantitative study using a pre-experimental design with a one- group pretest-posttest approach. The sample consisted of 58 pregnant women at 28 weeks of gestation from the service area of Puskesmas Pulosari, selected using purposive sampling. A questionnaire was used as the research instrument. Data analysis was conducted using univariate and bivariate methods with the Wilcoxon test. Results: The majority of respondents were aged 20–35 years (82.8%), had a secondary level of education (69%), were unemployed (91.4%), and were multiparous (50%). Before the video-based educational intervention, most respondents had a moderate level of knowledge (56.9%) and chose non-MKJP (79.3%). After the intervention, most demonstrated a good level of knowledge (58.6%) and chose MKJP (81%). Conclusion: A video-based education significantly improves knowledge levels and affects the selection of long-term contraceptive methods among third-trimester pregnant women at Pulosari Community Health Center.